Preparation method of modified hard carbon negative electrode material, negative electrode sheet containing the same, and sodium ion battery

Through the in situ modification of the hard carbon material through the silicane coupling agent, the problem of the first time Kuron's low efficiency and poor safety performance in the sodium ion battery in sodium ion batteries were solved, and the sodium battery multiplier performance, capacity, and circulatory performance were realized. Effect.

CN118851176BActive Publication Date: 2025-01-24WUXI ZHAONA NEW ENERGY TECHNOLOGY CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411321533.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2025-01-24
Estimated Expiration
2044-09-23

AI Technical Summary

Technical Problem

Hard carbon anode material has problems of low efficiency and poor safety performance in sodium ion batteries for the first time, and the existing improvement methods are costly or affect the material structure, affecting the capacity and cycle life of the battery.

Method used

By using a silicane coupling agent to modify the hard carbon front drive body in situ, a dehydration and contraction response of the SI-OH bond and the surface of the hard carbon material is generated to prepare the modified hard carbon negative material. This method includes crushing and carbonized hard carbon front -drives, pickling and activating treatment, and then reacting with a siane coupling agent to form a modified material.

Benefits of technology

It significantly improves the rate performance, capacity and cycle performance of sodium batteries, reduces side reactions during the first charge and discharge process, stabilizes the SEI film, and improves the Coulombic efficiency and cycle stability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118851176B_ABST
    Figure CN118851176B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of secondary batteries, and discloses a preparation method of a modified hard carbon negative electrode material, a negative electrode sheet and a sodium ion battery containing the same. The preparation method comprises the following steps: using a silane coupling agent to modify a hard carbon precursor in situ, and using the Si-OH bond generated after the hydrolysis of silane to react with hydroxyl groups, carboxyl groups and other groups on the surface of the hard carbon material to undergo a dehydration condensation reaction to obtain a modified hard carbon negative electrode material. The modification of the silane coupling agent has a significant enhancing effect on the sodium storage performance of the material, and can significantly increase the gram capacity; and during the modification process, the silane coupling agent and the functional groups on the surface of the hard carbon material undergo a coupling reaction, which reduces the side reactions during the first charging process, and at the same time, the introduction of the silane coupling agent improves the wettability of the electrolyte, which can significantly improve the first coulomb efficiency and cycle performance. In addition, the silane coupling agent can inhibit the growth of the SEI film and improve the rate performance of the material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of secondary batteries, and in particular relates to a method for preparing a modified hard carbon negative electrode material and a negative electrode sheet and a sodium ion battery containing the same. Background Art

[0002] As a new type of carbon negative electrode material, hard carbon has received widespread attention in recent years due to its unique microstructure and electrochemical properties. Hard carbon has high reversible capacity, good rate performance, excellent safety and low cost in the application field of sodium ion batteries, showing broad application prospects. However, there are also some shortcomings: 1. Low first coulombic efficiency: hard carbon materials will produce large irreversible capacity loss during the first charge and discharge process, and the first coulombic efficiency is usually only about 70% to 85%. This is mainly due to the formation of an irreversible solid electrolyte interface film (SEI film) on the surface of hard carbon materials, which consumes a large amount of lithium ions. 2. Safety issues: hard carbon materials will undergo irreversible electrochemical reactions under high potential conditions, generating a lot of heat, so they are prone to thermal runaway reactions, which poses certain safety hazards.

[0003] In view of the low initial efficiency and poor safety performance of hard carbon negative electrode materials, the common technical directions are: ① Use metals (Pb, Al, etc.) to modify the materials, but the cost of metals is high and a higher processing temperature is required during the processing, which increases the cost of the materials. ② Optimize the morphology of the materials. Common material spheroidization processes usually use ball milling, coating, etc. This type of method will cause changes in the material structure, thereby affecting the lithium / sodium storage effect, and then affecting the battery's capacity and cycle life; or directly synthesize spherical precursors. This method is costly and has a low yield and is not suitable for large-scale production. Therefore, in view of the above shortcomings, further research on hard carbon materials is needed to improve the comprehensive performance of hard carbon materials, which is conducive to the widespread application of hard carbon materials in sodium-ion batteries. Summary of the invention

[0004] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention provides a method for preparing a modified hard carbon negative electrode material, a negative electrode sheet containing the same, and a sodium ion battery. The modified hard carbon negative electrode material prepared by the present invention can effectively improve the rate performance, capacity and cycle performance of a sodium battery.

[0005] The invention provides a method for preparing a modified hard carbon negative electrode material.

[0006] Specifically, a method for preparing a modified hard carbon negative electrode material comprises the following steps:

[0007] The hard carbon precursor is modified in situ using a silane coupling agent, and the Si-OH bonds generated by the hydrolysis of silane react with the hydroxyl, carboxyl and other groups on the surface of the hard carbon material to undergo a dehydration condensation reaction to obtain a modified hard carbon negative electrode material.

[0008] More specifically, the method for preparing the modified hard carbon negative electrode material comprises the following steps:

[0009] crushing and carbonizing a hard carbon precursor to obtain a carbide;

[0010] hydrolyzing the silane coupling agent to obtain a silane coupling agent hydrolyzate;

[0011] The carbide is acid-washed to obtain a carbide to be modified; the carbide to be modified is subjected to a condensation reaction with the silane coupling agent hydrolyzate at a pH of 2 to 4, and after the reaction is completed, the modified hard carbon negative electrode material is obtained by washing and drying;

[0012] The chemical formula of the silane coupling agent is YR-Si(OR)3, wherein Y is a saturated non-oxygen-containing functional group and R is an alkyl group.

[0013] Preferably, the hard carbon precursor includes at least one of a biomass raw material, a resin raw material, and a mineral raw material. The biomass raw material includes coconut shell, rice shell, peanut shell, lignin or sugar, etc.; the resin raw material includes phenolic resin and / or epoxy resin; and the mineral raw material includes asphalt or coal.

[0014] Preferably, the carbonization temperature ranges from 550 to 700° C., and the carbonization time ranges from 2 to 6 hours.

[0015] Preferably, the pickling process is: pickling with dilute hydrochloric acid, dilute nitric acid, dilute sulfuric acid, or hydrofluoric acid. For example, dilute hydrochloric acid with a concentration of 1% to 5% is used, and the pickling treatment is performed according to a mass ratio of the dilute hydrochloric acid to the carbide of (1:1) to (5:1).

[0016] Preferably, the carbide further includes an activation treatment step before pickling, and the activation treatment includes physical activation treatment and chemical activation treatment. The process of the physical activation treatment is to activate the carbide at a mass ratio of (1:1.5) to (1:4) under the action of water vapor at 600 to 900°C for 1 to 5 hours. The process of the chemical activation treatment is to activate the carbide at a mass ratio of (1:1.5) to (1:4) under the action of alkali at 600 to 900°C for 1 to 5 hours. Activating the carbide can form a pore structure and pores of different particle sizes inside the hard carbon material, such as a large number of micropores or mesopores (with adjustable pore size), which can increase the specific surface area of ​​the material. On the one hand, the generation of pores can increase the storage capacity of the material for sodium ions, thereby increasing the capacity; on the other hand, the high specific surface area can also increase the contact between the hard carbon material and the silane coupling agent. After the silane coupling agent is added, the coupling agent is hydrolyzed to generate Si-OH, which undergoes a condensation reaction with the oxygen-containing functional groups on the surface of the hard carbon material, so that the surface of the carbon material generates functional groups with good binding properties with organic matter. This structure can reduce the side reactions between the hard carbon material and the electrolyte solvent / additive, stabilize the SEI film, and greatly improve the coulombic efficiency and cycle stability of the material. The base can be selected from potassium hydroxide, sodium hydroxide, etc.

[0017] Preferably, when the hard carbon precursor is a mineral raw material (such as coal tar pitch), a pre-oxidation step is also included before the carbide is activated. Specifically, the pre-oxidation process is: placing the carbide in an oxygen and inert atmosphere, pre-oxidizing it at 450-650°C for 1-4 hours to obtain a pre-oxidized material. The carbide prepared with mineral raw materials as the hard carbon precursor has a relatively regular arrangement of carbon atoms. By adding a pre-oxidation step during the preparation process, the CC bond between oxygen and the carbon layer undergoes an oxidation reaction, which can adjust the carbon layer structure and increase the disorder of carbon, thereby improving the material's ultimate storage capacity for sodium ions, and also improving the rate performance of sodium batteries.

[0018] Preferably, the silane coupling agent is aminosilane and / or vinylsilane. The aminosilane includes γ-aminopropyltriethoxysilane (KH550); the vinylsilane includes vinyltriethoxysilane.

[0019] Preferably, the mass ratio of the silane coupling agent to the carbonized material to be modified is (0.1:99.9) to (1.5:98.5). Further preferably, the mass ratio of the silane coupling agent to the carbonized material to be modified is (0.5:99.5) to (1.5:98.5); more preferably, the mass ratio of the silane coupling agent to the carbonized material to be modified is (0.8:99.2) to (1.2:98.8).

[0020] Preferably, the hydrolysis process of the silane coupling agent is: dissolving the silane coupling agent in a solvent, and hydrolyzing for 20 to 60 minutes at a pH of 2 to 4. The solvent includes alcohols (ethanol, methanol) or weak acids (acetic acid, oxalic acid). The mass of the silane coupling agent accounts for 1% to 30% of the mass of the solvent.

[0021] Preferably, the pH of the condensation reaction is 2 to 3, the temperature of the condensation reaction is 20 to 120° C., and the time of the condensation reaction is 30 min to 3 h.

[0022] The invention also provides a method for preparing a silicon dioxide-coated hard carbon material.

[0023] Specifically, a method for preparing a silicon dioxide-coated hard carbon material comprises the following steps:

[0024] The modified hard carbon negative electrode material prepared by the above preparation method is subjected to high temperature curing treatment to form a silicon dioxide coating layer to obtain a silicon dioxide coated hard carbon material.

[0025] Preferably, the high temperature curing process is: in an inert atmosphere, 500-900°C, high temperature curing for 1-5 hours; further preferably, the high temperature curing process is: in an inert atmosphere, 700-900°C, high temperature curing for 1.5-3 hours.

[0026] The present invention also provides a negative electrode material for a sodium ion battery, including a modified hard carbon negative electrode material prepared by the above-mentioned method for preparing a modified hard carbon negative electrode material or a silica-coated hard carbon material prepared by the above-mentioned method for preparing a silica-coated hard carbon material. The present invention uses the modified hard carbon material or the silica-coated hard carbon material as the negative electrode material for a sodium ion battery. Compared with conventional hard carbon materials, the surface of the modified hard carbon negative electrode material provided by the present invention has very few oxygen-containing functional groups. This is because the introduction of a silane coupling agent causes a coupling reaction with the original oxygen-containing functional groups on the surface of the hard carbon material, thereby removing the side reaction between oxygen and the electrolyte; the lipophilic group at the other end of the coupling agent has good compatibility with the electrolyte, thereby improving the wettability of the electrolyte. In addition, the coupling agent can inhibit the growth of the SEI film and improve the rate performance of the material.

[0027] The present invention also provides a negative electrode sheet, comprising the above-mentioned negative electrode material for a sodium ion battery. The negative electrode sheet comprises a negative electrode current collector and a negative electrode material layer bonded to the surface of the current collector; wherein the negative electrode material layer comprises a negative electrode active material, a binder and a conductive agent; and the negative electrode active material comprises the above-mentioned modified hard carbon negative electrode material or the above-mentioned silicon dioxide-coated hard carbon material.

[0028] The negative electrode current collector is a structure or part that collects current, and the negative electrode current collector can be any material suitable for use as a negative electrode current collector for sodium ion batteries in the art. For example, the negative electrode current collector includes but is not limited to metal foil, and more specifically includes but is not limited to aluminum foil.

[0029] The negative electrode sheet provided by the present invention can be prepared according to the conventional preparation of negative electrode sheets, such as by the following method: the negative electrode active material, the conductive agent, and the binder are prepared into a slurry according to a proportion, and then coated, rolled, and die-cut at a certain surface density to obtain a negative electrode sheet. In the slurry, the negative electrode active material can account for 90-99wt%, the conductive agent accounts for 0.05-5wt%; and the binder accounts for 0.5-5wt%. Among them, the binder includes but is not limited to at least one of SBR, PAA, PI, PAN, and PVDF, and the conductive agent includes but is not limited to at least one of carbon black (such as Super-P, KS-6), VGCF, multi-walled CNT, and single-walled CNT. It will not be repeated here.

[0030] The present invention also provides a sodium ion battery, comprising a positive electrode sheet, the negative electrode sheet and a separator spaced between the positive electrode sheet and the negative electrode sheet.

[0031] The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer coated on at least one surface of the positive electrode current collector. The positive electrode active material in the positive electrode active material layer can be a conventional positive electrode material for sodium ion batteries, such as a layered composite metal oxide. The positive electrode current collector can be any material suitable for use as a positive electrode current collector for sodium ion batteries in the art, for example, the positive electrode current collector includes but is not limited to metal foil, and more specifically includes but is not limited to aluminum foil.

[0032] The separator can be any material suitable for sodium ion battery separators in the art. For example, the separator includes but is not limited to a combination of one or more of polyethylene, polypropylene, polyvinylidene fluoride, aramid, polyethylene terephthalate, polytetrafluoroethylene, polyacrylonitrile, polyimide, polyamide, polyester and natural fibers.

[0033] Compared with the prior art, the present invention has the following beneficial effects:

[0034] Compared with conventional hard carbon materials, the modification of silane coupling agent has a significant enhancement effect on the sodium storage performance of the material, which can significantly increase the gram capacity; and during the modification process, the silane coupling agent reacts with the functional groups on the surface of the hard carbon material, reducing the side reactions during the first charge process. At the same time, the introduction of silane coupling agent improves the wettability of the electrolyte, which can significantly improve the first coulomb efficiency and cycle performance. In addition, the silane coupling agent can inhibit the growth of the SEI film and improve the rate performance of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 This is a flow chart of preparing a coupling agent-modified hard carbon material according to Example 3;

[0036] Figure 2 Schematic diagram of the hydrolysis reaction of γ-aminopropyltriethoxysilane in Examples 1 to 5;

[0037] Figure 3 Schematic diagram of the reaction of modifying hard carbon with γ-aminopropyltriethoxysilane in Examples 1 to 5;

[0038] Figure 4 XRD patterns of the hard carbon materials before and after modification of Comparative Example 1 (before modification) and Example 1 (after modification);

[0039] Figure 5 This is the SEM image of the modified hard carbon material in Example 1;

[0040] Figure 6 FTIR graphs of the hard carbon materials before and after modification of Comparative Example 1 (before modification) and Example 1 (after modification);

[0041] Figure 7 The charge and discharge curves before and after modification of Comparative Example 1 (before modification) and Example 1 (after modification);

[0042] Figure 8 The silica-coated hard carbon material prepared in Example 12. DETAILED DESCRIPTION

[0043] In order to make the technical scheme of the present invention more clearly understood by those skilled in the art, the following embodiments are listed for illustration. It should be pointed out that the following embodiments do not limit the protection scope of the present invention.

[0044] In order to make the technical scheme and advantages of the present invention clearer, the present invention and its beneficial effects are further described in detail below in conjunction with specific embodiments and drawings of the specification, but the embodiments of the present invention are not limited thereto. The raw materials, reagents or devices used in the following examples and comparative examples can be obtained from conventional commercial channels or can be obtained by existing known methods unless otherwise specified.

[0045] Example 1

[0046] This embodiment provides a method for preparing a modified hard carbon negative electrode material, comprising the following steps:

[0047] S01: Coconut shell is selected as raw material and crushed to obtain coconut shell powder, wherein the particle size D50 is 1 to 3 mm;

[0048] S02: subjecting the coconut shell powder prepared in S01 to high-temperature carbonization treatment in an inert atmosphere at a temperature of 550°C for 2.5 hours to obtain carbonized coconut shell;

[0049] S03: The carbonized coconut shell obtained in S02 is acid-washed in 3% dilute HCl, and the mass ratio of dilute HCl to carbonized coconut shell is 1:1;

[0050] S04: washing with 50 times deionized water until neutral, to obtain the carbonized coconut shell to be modified;

[0051] S05: Dissolve the silane coupling agent γ-aminopropyltriethoxysilane in anhydrous ethanol and deionized water (the mass ratio of anhydrous ethanol to deionized water is 1:1), adjust the pH value to 2 with 3% dilute hydrochloric acid, and mix for 20 minutes for hydrolysis (hydrolysis diagram as shown in Figure 2 As shown), a silane coupling agent hydrolyzate with a mass fraction of 3% was obtained;

[0052] S06: Mix the carbonized coconut shell to be modified with the hydrolyzed solution of γ-aminopropyltriethoxysilane obtained in S05 (the mass ratio of carbonized coconut shell to be modified: silane coupling agent is 99.5:0.5), and carry out condensation reaction. The condensation reaction conditions are: inert atmosphere, pH=2, reaction temperature: 120°C, reaction time: 1h. The reaction diagram of γ-aminopropyltriethoxysilane modification of hard carbon is shown in the figure. Figure 3 As shown;

[0053] S07: The material obtained in S06 is washed and dried with deionized water, crushed (D50: 5-6 μm) and demagnetized to obtain a coupling agent-modified hard carbon material.

[0054] Example 2

[0055] This embodiment provides a method for preparing a modified hard carbon negative electrode material, comprising the following steps:

[0056] S01: Coal tar is selected as raw material and crushed to obtain coal tar powder, wherein the particle size D50 is 1 to 3 mm;

[0057] S02: subjecting the coal tar powder prepared in S01 to high-temperature carbonization treatment in an inert atmosphere at a temperature of 550°C for 2.5 hours to obtain carbonized coal tar;

[0058] S03: pre-oxidizing the carbonized coal tar pitch prepared in S02 under the conditions of 1% oxygen + 99% inert atmosphere at a treatment temperature of 500°C for 2 hours to obtain a pre-oxidized material;

[0059] S04: The pre-oxidized material obtained in S03 is pickled in 3% dilute HCl, and the mass ratio of the acid solution to the pre-oxidized material is 1:1;

[0060] S05: washing with 50 times deionized water until neutral and drying to obtain the carbonized coal tar pitch to be modified;

[0061] S06: dissolving the silane coupling agent γ-aminopropyltriethoxysilane in anhydrous ethanol and deionized water (the mass ratio of anhydrous ethanol to deionized water is 1:1), adjusting the pH value to 2 with 3% dilute hydrochloric acid, mixing for 20 minutes for hydrolysis, and obtaining a silane coupling agent hydrolyzate with a mass fraction of 3%;

[0062] S07: Mix the carbonized coal tar pitch to be modified with the hydrolyzed solution of γ-aminopropyltriethoxysilane obtained as a silane coupling agent in S06 (the mass ratio of carbonized coal tar pitch to be modified: silane coupling agent is 99.5:0.5), and carry out condensation reaction. The reaction conditions are: inert atmosphere, pH=2, reaction temperature: 120°C, and reaction time: 1h;

[0063] S08: The material obtained in S07 is washed and dried using a deionized water solution, crushed (D50: 5-6 μm) and demagnetized to obtain a coupling agent-modified hard carbon material.

[0064] Example 3

[0065] This embodiment provides a method for preparing a coupling agent modified hard carbon negative electrode material (the flow chart is as follows Figure 1 ), including the following steps:

[0066] S01: Coconut shell is selected as raw material and crushed to obtain coconut shell powder, wherein the particle size D50 is 1 to 3 mm;

[0067] S02: subjecting the coconut shell powder prepared in S01 to high-temperature carbonization treatment in an inert atmosphere at a temperature of 550°C for 2.5 hours to obtain carbonized coconut shell;

[0068] S03: Activate the carbonized coconut shell obtained in S02 under water vapor conditions, the treatment conditions are: water vapor: nitrogen = 1.5:1, temperature 850°C, time 3h, to obtain activated carbonized coconut shell;

[0069] S04: The carbonized coconut shell obtained in S03 was acid-washed in 3% dilute HCl, and the mass ratio of acid solution to carbonized coconut shell was 1:1;

[0070] S05: washing with 50 times deionized water until neutral and drying to obtain the carbonized coconut shell to be modified;

[0071] S06: dissolving the silane coupling agent γ-aminopropyltriethoxysilane in anhydrous ethanol and deionized water (the mass ratio of anhydrous ethanol to deionized water is 1:1), adjusting the pH value to 2 with 3% dilute hydrochloric acid, mixing for 20 minutes for hydrolysis, and obtaining a silane coupling agent hydrolyzate with a mass fraction of 3%;

[0072] S07: Mix the carbonized coconut shell to be modified with the hydrolyzed solution of γ-aminopropyltriethoxysilane obtained in S06 (the mass ratio of carbonized coconut shell to be modified to silane coupling agent is 99.5:0.5) to carry out condensation reaction. The condensation reaction conditions are: inert atmosphere, pH=2, reaction temperature: 120°C, reaction time: 1h;

[0073] S08: The material obtained in S07 is washed and dried using a deionized water solution, crushed (D50: 5-6 μm) and demagnetized to obtain a coupling agent-modified hard carbon material.

[0074] Example 4

[0075] This embodiment provides a method for preparing a hard carbon negative electrode material, comprising the following steps:

[0076] S01: Coal tar is selected as raw material and crushed to obtain coal tar powder, wherein the particle size D50 is 1 to 3 mm;

[0077] S02: subjecting the coal tar powder prepared in S01 to high-temperature carbonization treatment in an inert atmosphere at a temperature of 550°C for 2.5 hours to obtain carbonized coal tar;

[0078] S03: pre-oxidizing the carbonized coal tar pitch prepared in S02 under the conditions of 1% oxygen + 99% inert atmosphere at a treatment temperature of 500°C for 2 hours to obtain a pre-oxidized material;

[0079] S04: After the pre-oxidized material obtained in S03 is mixed with KOH (the mass ratio of the pre-oxidized material to KOH is 1:3), activation is performed under the following treatment conditions: temperature 850°C, time 3h, to obtain the activated pre-oxidized material;

[0080] S05: The pre-oxidized material obtained in S04 is pickled in 3% dilute HCl, and the mass ratio of the acid solution to the pre-oxidized material is 1:1;

[0081] S06: Rinse with 50 times deionized water until neutral and dry, crush (D50: 5-6 μm) and demagnetize to obtain the carbonized coal tar to be modified.

[0082] S07: dissolving the silane coupling agent γ-aminopropyltriethoxysilane in anhydrous ethanol and deionized water (the mass ratio of anhydrous ethanol to deionized water is 1:1), adjusting the pH value to 2 with 3% dilute hydrochloric acid, mixing for 20 minutes for hydrolysis, and obtaining a silane coupling agent hydrolyzate with a mass fraction of 3%;

[0083] S08: Mix the carbonized coal tar pitch to be modified with the hydrolyzed solution of γ-aminopropyltriethoxysilane, a silane coupling agent, obtained in S07 (the mass ratio of the carbonized coal tar pitch to be modified to the silane coupling agent is 99.5:0.5), and carry out a condensation reaction. The condensation reaction conditions are: inert atmosphere, pH=2, reaction temperature of 120°C, and reaction time of 1h;

[0084] S09: The material obtained in S08 is washed and dried using a deionized water solution, crushed (D50: 5-6 μm) and demagnetized to obtain a coupling agent-modified hard carbon material.

[0085] Example 5

[0086] S01: Commercial hard carbon material (Kuraray, type 2) was selected as the raw material, and the button battery test method mentioned in the present invention was used for calibration, with a gram capacity of 285 mAh / g and a first efficiency of 86%;

[0087] S02: The commercial hard carbon material in S01 is acid-washed in 3% dilute HCl, and the mass ratio of the acid solution to the commercial hard carbon material is 1:1;

[0088] S03: washing with 50 times deionized water until neutral and drying to obtain the carbide to be modified;

[0089] S04: dissolving the silane coupling agent γ-aminopropyltriethoxysilane in anhydrous ethanol and deionized water (the mass ratio of anhydrous ethanol to deionized water is 1:1), adjusting the pH value to 2 with 3% dilute hydrochloric acid, mixing for 20 minutes for hydrolysis, and obtaining a silane coupling agent hydrolyzate with a mass fraction of 3%;

[0090] S05: Mix the modified carbide with the hydrolyzate of γ-aminopropyltriethoxysilane obtained in S04 (the mass ratio of the modified carbide to the silane coupling agent is 99.5:0.5) to carry out a condensation reaction. The condensation reaction conditions are: inert atmosphere, pH=2, reaction temperature of 120°C, and reaction time of 1h;

[0091] S06: The material obtained in S05 is washed and dried using a deionized water solution, crushed (D50: 5-6 μm) and demagnetized to obtain a coupling agent-modified hard carbon material.

[0092] Example 6

[0093] Different from Example 1, the silane coupling agent used in S05 is 3-methylpropyltrimethoxysilane.

[0094] Example 7

[0095] Different from Example 1, the ratio of carbonized coconut shell to silane coupling agent in S06 is 99:1.

[0096] Example 8

[0097] The difference from Example 1 is that the pH in S06 is 2, the treatment temperature is 80° C., and the treatment time is 2 h.

[0098] Example 9

[0099] Different from Example 1, Example 9 also includes step S08, and the process is: subjecting the coupling agent-modified hard carbon material obtained in Example 1 to high-temperature curing treatment under the following conditions: in an inert atmosphere, at a temperature of 600° C., and subjecting the high-temperature curing treatment to 2 h.

[0100] Example 10

[0101] The difference from Example 1 is that the silane coupling agent type is replaced by an equal amount of vinyltriethoxysilane.

[0102] Embodiment 11

[0103] Different from Example 2, the coupling agent modified hard carbon material obtained in Example 2 is subjected to high temperature curing treatment under the following conditions: in an inert atmosphere, at a temperature of 800° C., and for 2 h.

[0104] Example 12

[0105] Different from Example 4, the coupling agent modified hard carbon material obtained in Example 4 is subjected to a high temperature curing treatment under the following conditions: an inert atmosphere, a temperature of 800° C., and a high temperature curing treatment for 2 h.

[0106] Embodiment 13

[0107] Different from Example 9, when the coupling agent-modified hard carbon material is subjected to high-temperature curing treatment, the temperature of the high-temperature curing treatment is adjusted to 800°C.

[0108] Comparative Example 1

[0109] This comparative example provides a method for preparing a hard carbon negative electrode material, comprising the following steps:

[0110] S01: Coconut shell is selected as raw material and crushed to obtain coconut shell powder, wherein the particle size D50 is 1 to 3 mm;

[0111] S02: subjecting the coconut shell powder prepared in S01 to high-temperature carbonization treatment in an inert atmosphere at a temperature of 550°C for 2.5 hours to obtain carbonized coconut shell;

[0112] S03: The carbonized coconut shell obtained in S02 was washed in 3% diluted HCl, and the ratio of acid to carbonized coconut shell was 1:1;

[0113] S04: Rinse with 50 times deionized water until neutral and dry, crush (D50: 5-6 μm) and demagnetize to obtain hard carbon material.

[0114] Comparative Example 2

[0115] This comparative example provides a method for preparing a hard carbon negative electrode material, comprising the following steps:

[0116] S01: Coal tar is selected as raw material and crushed to obtain coal tar powder, wherein the particle size D50 is 1 to 3 mm;

[0117] S02: subjecting the coal tar powder prepared in S01 to high-temperature carbonization treatment in an inert atmosphere at a temperature of 550°C for 2.5 hours to obtain carbonized coal tar;

[0118] S03: pre-oxidizing the carbonized coal tar pitch prepared in S02 under the conditions of 1% oxygen + 99% inert atmosphere at a treatment temperature of 500°C for 2 hours to obtain a pre-oxidized material;

[0119] S04: The pre-oxide obtained in S03 is cleaned in 3% dilute HCl, and the ratio of acid to pre-oxide is 1:1;

[0120] S05: Rinse with 50 times deionized water until neutral and dry, crush (D50: 5-6 μm) and demagnetize to obtain hard carbon material.

[0121] Comparative Example 3

[0122] This comparative example provides a method for preparing a hard carbon negative electrode material, comprising the following steps:

[0123] S01: Coconut shell is selected as raw material and crushed to obtain coconut shell powder, wherein the particle size D50 is 1 to 3 mm;

[0124] S02: subjecting the coconut shell powder prepared in S01 to high-temperature carbonization treatment in an inert atmosphere at a temperature of 550°C for 2.5 hours to obtain carbonized coconut shell;

[0125] S03: Activate the carbonized coconut shell obtained in S02 under water vapor conditions, the treatment conditions are: water vapor: nitrogen = 1.5:1, the treatment temperature is 850°C, the treatment time is 3h, and the activated carbonized coconut shell is obtained;

[0126] S04: The carbonized coconut shell obtained in S03 was washed in 3% dilute HCl, and the ratio of acid solution to carbonized coconut shell was 1:1;

[0127] S05: Rinse with 50 times deionized water until neutral and dry, crush (D50: 5-6 μm) and demagnetize to obtain hard carbon material.

[0128] Comparative Example 4

[0129] This comparative example provides a method for preparing a hard carbon negative electrode material, comprising the following steps:

[0130] S01: Coal tar is selected as raw material and crushed to obtain coal tar powder, wherein the particle size D50 is 1 to 3 mm;

[0131] S02: subjecting the coal tar powder prepared in S01 to high-temperature carbonization treatment in an inert atmosphere at a temperature of 550°C for 2.5 hours to obtain carbonized coal tar;

[0132] S03: pre-oxidizing the carbonized coal tar pitch prepared in S02 under the conditions of 1% oxygen + 99% inert atmosphere at a treatment temperature of 500°C for 2 hours to obtain a pre-oxidized material;

[0133] S04: After the pre-oxide obtained in S03 is mixed with KOH (the mass ratio of the material to be treated to KOH is 1:3), activation is performed under the following treatment conditions: temperature 850°C, time 3h, to obtain the activated pre-oxide;

[0134] S05: The pre-oxide obtained in S04 is cleaned in 3% dilute HCl, and the ratio of acid to pre-oxide is 1:1;

[0135] S06: Rinse with 50 times deionized water until neutral and dry, crush (D50: 5-6 μm) and demagnetize to obtain hard carbon material.

[0136] Comparative Example 5

[0137] The difference from Example 1 is that the pH value of SO5 in Example 1 is adjusted to 7.5, and the remaining steps are the same as Example 1.

[0138] Comparative Example 6

[0139] The difference from Example 1 is that the silane coupling agent γ-aminopropyltriethoxysilane in Example 1 is replaced by an equal amount of epoxysilane (KH560).

[0140] Comparative Example 7

[0141] The difference from Example 1 is that the pH value in S05 is adjusted to 5.

[0142] The materials obtained in the above Examples 1 to 13 and Comparative Examples 1 to 7 are used as negative electrode materials for sodium ion batteries and applied to negative electrode sheets.

[0143] Among them, the preparation method of the negative electrode sheet is: under the same conditions, the negative electrode material, SBR+CMC and SP-P are mixed in a mass ratio of 95:3:2 to obtain a negative electrode slurry, the negative electrode slurry is coated on the surface of the aluminum foil, and after rolling, it is vacuum dried at 110°C for 12 hours to obtain a negative electrode sheet.

[0144] The obtained negative electrode sheet is applied to a sodium ion battery. A sodium foil is used as the positive electrode, polypropylene is used as the separator, and a non-aqueous electrolyte is used as the electrolyte (the specific preparation method is: ethylene carbonate and ethyl methyl carbonate are mixed in a volume ratio of 3:7, and NaPF6 is added to form an electrolyte, and the concentration of NaPF6 is 1 mol / L), and a sodium ion battery is made. The specific process can be referred to the existing preparation method, which will not be repeated here.

[0145] The obtained sodium ion battery was tested for gram capacity, first cycle efficiency, charging rate, and cycle life.

[0146] Specific test method:

[0147] (1) Gram capacity and first charge and discharge efficiency test: Place the sodium ion battery in a 25°C environment for 8 hours, discharge to 0V at 0.xC (x=1-3), discharge to 0V at 0.0xC (x=1-3); let stand for 5 minutes; charge to 2V at 0.xC (x=1-3). The charge capacity is taken as the final gram capacity value, and the ratio of the charge capacity to the discharge capacity is taken as the first charge and discharge efficiency value.

[0148] (2) Charging rate and cycle performance test: Place the sodium ion battery in an environment of 25°C, charge it to 4.0V at a constant current and voltage of xC (1C to 3C), set the cut-off current to 0.05C, and discharge it to 1.5V at a constant current of 0.7C. This charge and discharge step is recorded as one cycle. Repeat this cycle until the capacity retention rate is less than 80%, and record the number of cycles.

[0149] The test results are shown in Table 1.

[0150] Table 1

[0151]

[0152] From the results in Table 1 above, it can be seen that in Examples 1 and 3, and Examples 2 and 4, Examples 3 and 4 add an activation process, adjust the material structure on the original basis, and create pores without affecting the arrangement of carbon atoms, so that a dendritic pore structure is generated inside the material particles, and the proportion of micropores (<2nm) reaches 95%. The formation of the pore structure can store more lithium / sodium ions and provide more capacity.

[0153] Comparing Example 1 and Example 2, in Example 2, since the carbon atoms of coal tar pitch are arranged more regularly, a pre-oxidation step is added in the preparation process, aiming to cause an oxidation reaction between oxygen and the CC bond between the carbon layer, so as to adjust the carbon layer structure, increase the disorder of the carbon, and thereby improve the material's ultimate storage capacity for sodium ions, while also improving the rate performance of lithium / sodium batteries.

[0154] Comparing Example 1 with Comparative Example 1, Example 2 with Comparative Example 2, Example 3 with Comparative Example 3, and Example 4 with Comparative Example 4, Examples 1 to 4 are subjected to coupling agent modification on the surface of the hard carbon material. Before modification, there are a large number of oxygen-containing groups such as hydroxyl and carboxyl groups on the surface of the hard carbon material, and the oxygen-containing groups are easy to react with the electrolyte, resulting in irreversible capacity loss, so the first coulomb efficiency is low; in addition, the oxygen-containing functional groups react with the electrolyte to produce gas, which affects the electrochemical performance of the battery. Figure 4 , Figure 6 The XRD and FTIR spectra of the modified materials of Comparative Example 1 (before modification) and Example 1 (after modification) are described respectively. Figure 5 is the SEM image of the modified material; Figure 4 , Figure 6 This indicates that the oxygen-containing functional groups disappear after modification, and the silane coupling agent has reacted with the functional groups on the hard carbon surface; and the arrangement and structure of carbon atoms will not be changed after modification. Figure 7 The charge-discharge curves of Comparative Example 1 (before modification) and Example 1 (after modification) before and after modification are shown in FIG. Figure 7 It can be seen that the modified silane coupling agent can significantly increase the gram capacity of the battery. Analysis of the reasons shows that the silane coupling agent first undergoes hydrolysis reaction (such as Figure 2 The reaction is shown in Figure ), followed by a polycondensation reaction with the functional groups on the hard carbon surface (such as Figure 3 The reaction shown in the figure removes the hidden dangers of low initial efficiency and poor cycle caused by the contact between oxygen and electrolyte; at the same time, the other end of the silane coupling agent has strong reaction inertness, good compatibility with the electrolyte, and high conductivity. Therefore, the hard carbon material modified with silane coupling agent has a higher initial coulomb efficiency on the one hand; on the other hand, it improves the infiltration with the electrolyte and reduces the probability of side reactions, so the cycle performance is also better.

[0155] Comparing Example 1 and Example 6, the γ-aminopropyltriethoxysilane used in Example 1 contains nitrogen groups, and the amino groups have strong polarity, so the conductivity is higher, and the battery has better rate performance.

[0156] Comparing Example 1 with Example 7, after the coupling agent content is increased in Example 7, the functional groups on the surface of the hard carbon are reacted more thoroughly, so both the first effect and the cycle performance are improved.

[0157] Comparing Example 1 with Example 9, Example 2 with Example 11, and Example 4 with Example 12, Examples 9, 11, and 12 subjected the modified materials to high temperature treatment, and the molecules on the surface of the hard carbon were degraded by heat to generate silicon dioxide, which was coated on the surface of the material ( Figure 8 , Figure 8 The surface of the coated material is dense and smooth, while the surface of the uncoated material is rough and has holes ( Figure 5 )), which has a certain inhibitory effect on the expansion of the material during the charge and discharge process, and has good wettability with the electrolyte, so the capacity and cycle performance are good. The material also eliminates the interference of oxygen-containing functional groups, so the capacity is improved. The presence of the coating increases the contact path with the electrolyte, so the rate is reduced.

[0158] Comparing Example 10 with Example 1, in Example 1, the amino group in contact with the electrolyte has strong polarity and does not react with the electrolyte components, so its rate performance is better. Vinyl is more inert, so the surface stability of the material is better after long-term circulation, the capacity and first effect are better, and the cycle performance of the battery is also better.

[0159] Comparing Example 13 with Example 9, increasing the temperature of the heat treatment allows for a more thorough formation of the silicon dioxide layer and, at the same time, has an effect of removing the remaining organic functional groups on the surface of the hard carbon material, thereby increasing the rate performance and improving the cycle performance.

[0160] Comparative Example 1 and Comparative Example 5, since the silane coupling agent does not undergo hydrolysis reaction under alkaline conditions ( Figure 2 To the right), a condensation reaction occurs to generate alcohol and ether products. In the subsequent reaction process, there are many side reactions with the electrolyte, so the capacity, first efficiency, and cycle performance are poor. It has little effect on rate performance.

[0161] Comparing Example 1 and Comparative Example 6, after the epoxy coupling agent is hydrolyzed and the carbon material is modified, the reaction product is esters. The ester functional groups have more side reactions with the electrolyte in the subsequent reaction process, so the capacity, first efficiency and cycle performance are all poor. The effect on the rate performance is small.

[0162] Comparing Example 1 and Comparative Example 7, the pH value of the solvent in Comparative Example 7 increases, such as Figure 2 The reaction shown cannot be fully carried out, so the amount of silane coupling agent connected to the hard carbon material is reduced, and the modification effect on the hard carbon is weakened. Therefore, the capacity is reduced and the rate performance is also deteriorated. The amino functional groups on the hard carbon surface are reduced, so the stability with the electrolyte is reduced and the cycle performance is reduced. Figure 2It is a reversible reaction. When the pH value is small within a certain range, the reaction is more favorable to the right reaction. Therefore, when the pH value is increased, the hydrolysis reaction product of the coupling agent is less, so there are fewer hydroxyl groups, so the amount of coupling agent that can react with the hard carbon is reduced. Then, the lipophilic groups on the surface of the modified hard carbon become less, and there are more side reactions during the first charge and discharge, which manifests as a small capacity and a reduced first efficiency. With fewer lipophilic groups, the conduction of ions is not as good as in Example 1, so the rate performance is also worse.

[0163] In summary, the gram capacity of the sodium ion battery provided by the present invention is greater than or equal to 273mAh / g, the capacity retention rate is not less than 80%, and the number of cycles is greater than or equal to 95 cycles. The negative electrode material for sodium ion batteries provided by the present invention can be prepared by multiple control of hard carbon precursors, hard carbon materials, silane coupling agents, and acids during the preparation process to obtain a sodium ion battery negative electrode material with better comprehensive chemical performance, taking into account rate performance, capacity, and cycle performance, especially for rate performance, providing a variety of choices for sodium ion batteries in the field of high rate requirements.

[0164] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for preparing a modified hard carbon negative electrode material, characterized in that: The following steps are involved: crushing and carbonizing a hard carbon precursor to obtain a carbide; hydrolyzing the silane coupling agent to obtain a silane coupling agent hydrolyzate; The carbide is acid-washed to obtain a carbide to be modified; the carbide to be modified is subjected to a condensation reaction with the silane coupling agent hydrolyzate at a pH of 2 to 4 and a temperature of 20 to 120° C. After the reaction is completed, the carbide is washed and dried to obtain a modified hard carbon negative electrode material; The chemical formula of the silane coupling agent is YR-Si(OR)3, wherein Y is a saturated non-oxygen-containing functional group and R is an alkyl group; The mass ratio of the silane coupling agent to the carbonized material to be modified is (0.1:99.9) to (1.5:98.5).

2. The method for preparing the modified hard carbon negative electrode material according to claim 1, characterized in that: The carbide further comprises an activation treatment step before pickling, and the activation treatment comprises a physical activation treatment or a chemical activation treatment.

3. The method for preparing the modified hard carbon negative electrode material according to claim 2, characterized in that: The physical activation treatment process is to perform the activation treatment at 600-900°C for 1-5 hours under the action of water vapor, with a mass ratio of water vapor to the carbide being (1:1.5)-(1:4); the chemical activation treatment process is to perform the activation treatment at 600-900°C for 1-5 hours under the action of alkali, with a mass ratio of the carbide to the alkali being (1:1.5)-(1:4).

4. The method for preparing a modified hard carbon negative electrode material according to any one of claims 1 to 3, characterized in that: The condensation reaction time is 30 minutes to 3 hours.

5. A method for preparing a silicon dioxide-coated hard carbon material, characterized in that: The following steps are involved: The modified hard carbon negative electrode material prepared by the method for preparing the modified hard carbon negative electrode material according to any one of claims 1 to 4 is subjected to high temperature curing treatment to form a silicon dioxide coating layer to prepare a silicon dioxide coated hard carbon material.

6. The method for preparing a silicon dioxide-coated hard carbon material according to claim 5, characterized in that: The high temperature curing process is: high temperature curing treatment in an inert atmosphere at 500-900° C. for 1-5 hours.

7. A negative electrode material for a sodium ion battery, characterized in that: The modified hard carbon negative electrode material comprises the modified hard carbon negative electrode material prepared by the preparation method of the modified hard carbon negative electrode material according to any one of claims 1 to 4 or the silica-coated hard carbon material prepared by the preparation method of the silica-coated hard carbon material according to claim 5 or 6.

8. A negative electrode sheet, characterized in that: Including the sodium ion battery negative electrode material according to claim 7.

9. A sodium ion battery, characterized in that: The invention comprises a positive electrode sheet, the negative electrode sheet as claimed in claim 8 and a separator spaced between the positive electrode sheet and the negative electrode sheet.

Citation Information

Patent Citations

  • Battery electrode and method of manufacturing the same

    JP2011049046A